Support Experiences for Novice Nurses in the Workplace: A Qualitative Analysis - Bahareh Najafi BScN, MScN, PhD; Ahmad Nasiri BScN, MScN, PhD (SAGE Publishing, 2023)
Introduction Since novice nurses need support at the beginning of their work, knowing workplace support resources can help them to experience fewer challenges at the beginning of their work and improve the quality of patient care. Objective(s) The present qualitative study aimed to explore novice nurses' experiences of supporting the workplace at the beginning of their work. Design This qualitative study was performed using a content analysis method. Methods This qualitative study was conducted with 14 novice nurse participants using the conventional content analysis method, unstructured in-depth interviews were used to collect data. All data were recorded, transcribed, and analyzed based on the Graneheim and Lundman method. Results Two major categories and four subcategories were extracted during data analysis as follows: (1) An intimate work environment with subcategories of cooperative work atmosphere and empathetic behaviors, (2) Educational support available for improvement contains subcategories conducting orientation courses and holding retraining courses. Conclusion The present study showed that such experiences as an intimate work environment, and educational support help novice nurses to have a supportive workplace and improve their performance. A welcoming and supportive atmosphere should be created for newcomers to ease their anxiety and frustration. Furthermore, they can improve their performance and provide quality care by giving themselves the motivation and spirit of improvement. Relevance to Clinical Practice This research highlights the need for new nurses to have support resources in the work environment, and healthcare managers can improve the quality of care by allocating sufficient support resources to this group of nurses.